Evidence-Based Library and Information Practice & Educational Needs of Health Librarians: National and International Trends - chaturvedi, kiran (DESIDOC Journal of Library & Information Technology, 2016)
The health care knowledge base, documented in the healthcare literature is vast and ever increasing and changing. Changes in medical information and technology are revolutionising health care. The clinicians today are trying to incorporate research into practice and are increasingly depend on technology to bring evidence to the bedside to improve quality and patient outcomes. Today, given the significance of evidence-based practice, health librarianship is given higher priority in many centers. Responses vary, but there seems to be a more towards ‘clinical information scientists’ - ‘informationists’ who might be educated in both clinical and information disciplines. But adaptation to change is not enough. Even as we have increased our roles in health environment as value-added educators and information providers, there is need to continue education and training in different facets: conferences, short courses, seminars etc should be conducted. Conferences are required to be organised at national level in order to improve health care services and recognition of health librarianship.